HERPES VIRUS INFECTION AND GLOMERULONEPHRITIS IN CHILDREN - V. Kruglikov; I. Bagdasarova; I. Kruglikova; I. Vasilyeva; O. Zyubko (Ukrainian Journal of Nephrology and Dialysis, 2015)
The article presents the analysis of the native and foreign literature data and also the results of our own research devoted to studying the role of herpes virus infection in the appearance and course of glomerulonephritis in children. There has been described pathogenesis and clinical aspects of virus associated glomerulonephritis in children. Much attention has been paid to the diagnostic methods of herpes virus infection in glomerulonephritis. The importance of association of immunosuppressive and antiviral therapy has been underlined.